An improved method for estimating internal solitary waves force on small circular cylindrical structures. (January 2023) - Cui, Junnan; Wang, Zhifeng; Dong, Sheng; Cheng, Junyu; Ren, Jiayin
Abstract: Theoretically calculation and laboratory experiments were performed to investigate the horizontal force exerted by internal solitary wave (ISW) on small circular cylindrical structures. Improvement in calculation of drag force and inertia force by introducing two-drag-coefficient method and spatial derivative of velocity into the calculation of force by eigenfunction was made based on systematically study on theoretical foundations. Particle image velocimetry (PIV) method and high precision force sensor were used to measure the velocity and force exerted by ISW, respectively. ISW waveform was traced by analyzing image frames follow grayscale threshold method. For the first time, components of horizontal force were calculated from PIV data, which show good agreement with theoretical one. Moreover, series comparisons between experimental data and calculational results were carried out to examine the proposed method. The results show ideal accuracy of the method and significant improvement comparing to the traditional method. Highlights: Improve calculation accuracy of inertia and drag force induced by ISW. Calculate force components from PIV data and compare with theoretical results. Ideal accuracy of the proposed method was validated by experimental data.